To switch or not to switch? Individual differences in executive function and emotion regulation flexibility - TOH, Wei Xing (Institutional Knowledge at Singapore Management University, 2024)
Emotion regulation (ER) constitutes strategies that modulate the experience and expression of emotions. While past work has predominantly assumed that ER strategies are consistently adaptive (or maladaptive) across situations, recent research has begun to examine individual-difference factors that are associated with the flexible use of ER strategies in line with contextual demands (i.e., ER flexibility). Theoretical accounts maintain that the choice to use ER strategies in a given context is contingent on individual differences in executive function (EF), which refers to a collection of general-purpose regulatory operations. Based on a comprehensive battery of EF tasks, we investigated how the various EF facets (i.e., common EF, working-memory-specific, and shifting-specific factors) are related to the frequency of maintaining and switching ER strategies in response to stimuli that elicit varying levels of emotional intensity. Results indicated that individuals with higher EF demonstrated a more flexible pattern of ER strategy use across high- and low-intensity conditions. Specifically, better working-memory-specific ability (i.e., manipulating information within a mental workspace) was associated with a greater frequency of reappraisal-to-distraction strategy switching in high-intensity contexts. Furthermore, more proficient common EF (i.e., sustaining relevant goals in the face of competing goals and responses) corresponded to a higher propensity to maintain the use of reappraisal in low-intensity situations. The outcomes of this study offer a first glimpse of the cognitive factors underlying ER flexibility. (PsycInfo Database Record (c) 2024 APA, all rights reserved).